Relative roles and limits of extension approaches in promoting sustainable agricultural management practices: Analysis of nationally representative panel data from Malawi - Ragasa, Catherine; Mzungu, Diston; Kalagho, Kenan; Kazembe, Cynthia (International Food Policy Research Institute, 2021)
Low-cost and sustainable agricultural management practices are being promoted in many countries but continue to face low adoption among farmers. We tracked the awareness and adoption among farmers of a number of practices―soil cover, minimum tillage, crop rotation, intercropping, crop diversification, crop residue incorporation, pit planting, water harvesting, and organic fertilizer―in two rounds of a nationally representative rural household survey in Malawi. Survey data and focus group discussions are used to understand the factors explaining the variations in farmers’ awareness and adoption of these practices. Results show a strong positive effect of extension services receipt on farmers’ awareness of these practices but no effect on farmers’ adoption of most of the practices being promoted, except for crop residue incorporation and organic fertilizer use. Receipt of input subsidy does not influence the adoption of these practices. Both survey data and focus group discussions highlight the need for intensive and iterative engagement between service providers and farmers to fully communicate, learn, and adapt to these management practices.